Expand your horizons with the diverse and informative answers found on IDNLearn.com. Get step-by-step guidance for all your technical questions from our dedicated community members.
Sagot :
To find the equation of the line that is perpendicular to the given line [tex]\( y - 4 = -\frac{2}{3}(x - 6) \)[/tex] and passes through the point [tex]\((-2, -2)\)[/tex], let's follow these steps:
1. Identify the slope of the given line:
The given line equation is in point-slope form:
[tex]\[ y - 4 = -\frac{2}{3}(x - 6) \][/tex]
The coefficient of [tex]\((x - 6)\)[/tex] is the slope of the line. So, the slope [tex]\( m_1 \)[/tex] of the given line is:
[tex]\[ m_1 = -\frac{2}{3} \][/tex]
2. Find the slope of the perpendicular line:
The slope of a line perpendicular to another is the negative reciprocal of the original slope. Therefore, the slope [tex]\( m_2 \)[/tex] of the perpendicular line is:
[tex]\[ m_2 = -\frac{1}{m_1} = -\frac{1}{-\frac{2}{3}} = \frac{3}{2} \][/tex]
3. Use the slope-intercept form (y = mx + b) to find the y-intercept:
The point [tex]\((-2, -2)\)[/tex] lies on the perpendicular line. Using this point and the slope [tex]\( \frac{3}{2} \)[/tex], we can find the y-intercept [tex]\( b \)[/tex]:
[tex]\[ y = mx + b \][/tex]
Substituting [tex]\((x_1, y_1) = (-2, -2)\)[/tex] and [tex]\( m_2 = \frac{3}{2} \)[/tex]:
[tex]\[ -2 = \frac{3}{2}(-2) + b \][/tex]
4. Solve for the y-intercept [tex]\( b \)[/tex]:
Calculate [tex]\( \frac{3}{2}(-2) \)[/tex]:
[tex]\[ \frac{3}{2} \times -2 = -3 \][/tex]
Substitute back into the equation to solve for [tex]\( b \)[/tex]:
[tex]\[ -2 = -3 + b \][/tex]
Adding 3 to both sides:
[tex]\[ b = 1 \][/tex]
5. Write the final equation:
With [tex]\( m_2 = \frac{3}{2} \)[/tex] and [tex]\( b = 1 \)[/tex], the equation of the line in slope-intercept form is:
[tex]\[ y = \frac{3}{2}x + 1 \][/tex]
Therefore, the equation of the line that is perpendicular to the given line and passes through the point [tex]\((-2, -2)\)[/tex] is:
[tex]\[ \boxed{y = \frac{3}{2}x + 1} \][/tex]
1. Identify the slope of the given line:
The given line equation is in point-slope form:
[tex]\[ y - 4 = -\frac{2}{3}(x - 6) \][/tex]
The coefficient of [tex]\((x - 6)\)[/tex] is the slope of the line. So, the slope [tex]\( m_1 \)[/tex] of the given line is:
[tex]\[ m_1 = -\frac{2}{3} \][/tex]
2. Find the slope of the perpendicular line:
The slope of a line perpendicular to another is the negative reciprocal of the original slope. Therefore, the slope [tex]\( m_2 \)[/tex] of the perpendicular line is:
[tex]\[ m_2 = -\frac{1}{m_1} = -\frac{1}{-\frac{2}{3}} = \frac{3}{2} \][/tex]
3. Use the slope-intercept form (y = mx + b) to find the y-intercept:
The point [tex]\((-2, -2)\)[/tex] lies on the perpendicular line. Using this point and the slope [tex]\( \frac{3}{2} \)[/tex], we can find the y-intercept [tex]\( b \)[/tex]:
[tex]\[ y = mx + b \][/tex]
Substituting [tex]\((x_1, y_1) = (-2, -2)\)[/tex] and [tex]\( m_2 = \frac{3}{2} \)[/tex]:
[tex]\[ -2 = \frac{3}{2}(-2) + b \][/tex]
4. Solve for the y-intercept [tex]\( b \)[/tex]:
Calculate [tex]\( \frac{3}{2}(-2) \)[/tex]:
[tex]\[ \frac{3}{2} \times -2 = -3 \][/tex]
Substitute back into the equation to solve for [tex]\( b \)[/tex]:
[tex]\[ -2 = -3 + b \][/tex]
Adding 3 to both sides:
[tex]\[ b = 1 \][/tex]
5. Write the final equation:
With [tex]\( m_2 = \frac{3}{2} \)[/tex] and [tex]\( b = 1 \)[/tex], the equation of the line in slope-intercept form is:
[tex]\[ y = \frac{3}{2}x + 1 \][/tex]
Therefore, the equation of the line that is perpendicular to the given line and passes through the point [tex]\((-2, -2)\)[/tex] is:
[tex]\[ \boxed{y = \frac{3}{2}x + 1} \][/tex]
Thank you for contributing to our discussion. Don't forget to check back for new answers. Keep asking, answering, and sharing useful information. Thank you for visiting IDNLearn.com. We’re here to provide dependable answers, so visit us again soon.